The combined effect of lead ion and sodium silicate in the flotation separation of scheelite from calcite. Issue 3 (11th February 2017) - Feng, Bo; Guo, Wei; Xu, Hongguo; Peng, Jinxiu; Luo, Xianping; Zhu, Xianwen
ABSTRACT: Flotation separation of scheelite from calcite is difficult because of the existence of the same cation in the minerals and similar physicochemical characteristics. Many studies have been performed to determine the selective depressants for calcite, but the separation of scheelite from calcite is still a big problem. In this article, the flotation separation of scheelite from calcite has been studied by flotation tests. The results show that benzohydroxamic acid has weak collecting ability to both scheelite and calcite. Lead ions can activate the flotation of scheelite and calcite, but the flotation separation of scheelite from calcite can't be realized. The depressant saline sodium silicate (mixture of sodium silicate and lead ions) has selective depression effect on calcite and the optimum ratio of sodium silicate to lead ions is 3:1. The use of saline sodium silicate as a depressant can achieve the flotation separation of scheelite from calcite. The zeta potential results and adsorption studies showed that the pre-adsorption of saline sodium silicate only interferes with the adsorption of benzohydroxamic acid on calcite surface; this is the main reason for the selective depression effect of saline sodium silicate on calcite.